1978
DOI: 10.1073/pnas.75.12.6197
|View full text |Cite
|
Sign up to set email alerts
|

Binding of HLA antigen-containing liposomes to bacteria

Abstract: Highly purified, detergent-solubilized HLA-A and -B antigens and HLA-D antigens were separately incorporated into liposomes. Deter The major histocompatibility complex (MHC) controls the expression of several types of cell surface glycoproteins that seem to have been highly conserved during evolution. In man, two types of MHC antigens have been distinguished. The HLA-A, -B, and -C antigens are composed of two types of polypeptide chains (1, 2). The larger subunit expresses the particular alloantigenic determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
4
0

Year Published

1979
1979
2022
2022

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(5 citation statements)
references
References 21 publications
1
4
0
Order By: Relevance
“…-B, and -C antigens thus seem the most likely participants in an interaction with streptococci. It has previously been reported that liposome-bound HLA antigens interact with strains of Branhatnetta catarrhalis and Haetnophiliis itifluenzae (streptococei were not included in the study), but this interaction seemed to involve the heavy HLA chain rather than /Jim [17], In the present work we found a very close correlation between /i^m binding and HLA binding, and HLA binding was also inhibited by jS^m. Our results favour the conclusion that /5;m in the HLA complex Is able to interact with streptocoecal surfaee structures.…”
Section: Discussionsupporting
confidence: 68%
“…-B, and -C antigens thus seem the most likely participants in an interaction with streptococci. It has previously been reported that liposome-bound HLA antigens interact with strains of Branhatnetta catarrhalis and Haetnophiliis itifluenzae (streptococei were not included in the study), but this interaction seemed to involve the heavy HLA chain rather than /Jim [17], In the present work we found a very close correlation between /i^m binding and HLA binding, and HLA binding was also inhibited by jS^m. Our results favour the conclusion that /5;m in the HLA complex Is able to interact with streptocoecal surfaee structures.…”
Section: Discussionsupporting
confidence: 68%
“…Based on enzymatic and serologinjection of carrageenan [59] or liposomes containing a ical data, MHC reconstituted into liposomes was found cytotoxic agent (dichloromethylene diphosphonate) to be at least partly or fully in a 'right side out' [60,611. These treatments resulted in severe suppresconfiguration similar to that found in cells [30,[33][34][35][36][37] [62]. In these experiments sarily excluded.…”
Section: Ij-d Interactions Of Liposomes With Antigen Presentingmentioning
confidence: 63%
“…Face-1, Face-2 and Face-3 can be incorporated onto liposomes [138,139] or extra cellular vesicles to be used as vaccines. Klareskog et al [140] have developed a protocol to making HLA-containing liposomes, which would be valuable to develop HLA-liposome vaccines to target the novel faces of HLA. More investigations are needed to fully understand the functional roles of these new faces of HLA-I in human diseases.…”
Section: Significance Of the Faces Of Hla-imentioning
confidence: 99%